THE EFFECTS OF COVID-19 PANDEMIC TOWARD LEARNING FROM HOME PROCESS IN JUNIOR HIGH SCHOOL IN AMBON CITY: AN EXPLORATION STUDY - Jotty Sartje Haumahu (Faculty of Teacher Training and Educational Sciences, Pattimura University Indonesia, 2020)
The purpose of this study was to identify and obtain information on the constraints of the online teaching and learning process at home as a result of the Covid-19 pandemic. The research use the exploratory case study method and the research approach utilised the qualitative case study method which was applied to obtain information on the constraints and consequences of the Covid-19 pandemic on teaching and learning activities in junior high school. In this study, respondents were 3 teachers and 3 parents at the Kusu-kusu Sereh Christian Middle School in Ambon. Semi-structured interviews were conducted and a list of questions compiled for interviews was developed based on related literature. The results of this study are that there are several obstacles experienced by students, teachers and parents in teaching and learning activities both online and offline. Obstacles in the online learning process are mainly the lacking technology mastery, the additional cost of internet quota, and lastly the reduced communication and socialization between students, teachers and parents. Obstacles in offline learning are the distance the teacher travels to when visiting the student's residence which is quite far away and the additional work for the teacher in arranging the schedule for student home visits. The same constraints faced in online and offline learning are the existence of additional work for parents in accompanying children to study, and unlimited working hours for teachers because they have to communicate and coordinate with parents, other teachers, and school principals